Management and minimization of concentrated stream from electrodialysis processes (CED/BMED) - Ilhan, Fatih (PAMUKKALE UNIV, 2018)
The most significant disadvantage of membrane processes is considered to be concentrated flow. In classical membrane processes where the driving force is pressure, a concentrated flow of 10-35% occurs. Similarly, in electrodeionization processes, where the driving force is electricity current, a concentrated flow of 10% is known to occur in practice. In this paper, studies were conducted on the reutilization of the concentrated part. Thus, the concentrated part was reduced to 0.5% and 1% in the classical electrodialysis and bipolar membrane electrodialysis processes, respectively. Furthermore, considering that the concentrated flow in the process is acidic and alkaline solutions, these solutions were concentrated. In consequence of the acid concentration process carried out in relation to the contaminant ion 0.01 M H and 0.01 M OH ion concentrations, an ion concentration of 0.72 M H could be achieved. Similarly, OH ion concentration rose to 0.5M. Thus, minimization of the concentrated part, one of the most important problems encountered in membrane processes, could be ensured simultaneously. Moreover, quite acidic and alkaline solutions were obtained simultaneously.
Keywords: Concentrated stream; Concentrated minimization; Electrodialysis; Bipolar membrane electrodialysis; WASTE-WATER; MEMBRANE PERFORMANCE; NF; RECOVERY; OSMOSIS; RECIRCULATION; EFFLUENT; Engineering